A inserção das questões ambientais no curso de Licenciatura em Química da Universidade Federal de Sergipe - Pitanga, Ângelo Francklin (2015)
The current economic system began in the mid-twentieth century to present unsustainability signals due to the realization of various externalities that go beyond the destruction and depletion of natural resources. In this scenario, the chemical-industrial activity due to its polluting action and some world level disaster is being questioned and required a new attitude towards the issues surrounding the care and preservation of the environment. In this context, this thesis aimed to investigate how environmental issues - Environmental Problems, Green Chemistry, Sustainable Development and Environmental Education - are being inserted in the course of degree in Chemistry offered by the Federal University of Sergipe on the campus of São Cristóvão. To this end, we sought to identify the concepts, methods and practices adopted by teachers. The Qualitative Research and interpretive served as the theoretical north in order to analyze in depth the research universe. In data collection were used: Documents and interviews analysis of semi-structured screen in the course teachers. In the analysis of the results there have based on the Textual Analysis Discourse. In order to meet the rigors and the internal validity of the research, the triangulation method was used so that the inferences and interpretations of the results guarantee the quality of the research. The diagnosis of curricular analysis was carried out by reference to the criteria proposed by the network Environmentalisation Curricular for Advanced Studies, pointing to an innovative curriculum that seeks to meet the legal requirements, but when broken down into its curriculum components, we see a low structure flexible where environmental issues are poorly covered. Regarding the analysis categories investigated, it is observed by teachers that treatment of environmental problems is limited to the development of their laboratory activities, micro context. An understanding of sustainable development that is widely criticized. And behaviorists views on environmental education. Generally that appear as anthropocentric conceptions, based on a technical-instrumental rationality, where technical solutions are sufficient to enable the current problems. Regarding the Green Chemistry, there are certain ignorance associated with its principles and philosophy, and their ideas framed in the developmental chain or pragmatic macro trend. The data collected both in research as in the references point out that the way they operated, the Green Chemistry is a rationalization instrument that could end up collaborating in maintaining the interests of hegemonic groups. As for the methods and practices have been reported the use of pedagogical interventions that encourage participation and the construction of knowledge by the students, however, is still marked concern about the transmission of disciplinary scientific content.